PERTANGGUNGJAWABAN HUKUM TERHADAP PENYALAHGUNAAN WEWENANG OLEH PENGGUNA ANGGARAN DALAM PENGADAAN BARANG DI KABUPATEN BREBES - Suwarni Suwarni (MIH Unsoed, 2019)
The implementation of a transparent government in the implementation of project tenders is an important issue that needs to be responded to immediately by the local government. This study aims to find out and analyze the abuse of authority by Budget Users in the procurement of goods in Brebes Regency. In addition, it is also to analyze the legal accountability of Budget Users against abuse of authority in the procurement of goods in Brebes Regency. The study uses a normative juridical approach, with secondary data sources and quantitative analysis.The results showed that, Abuse of authority by Budget Users in the procurement of goods in Brebes Regency was a category of abuse of authority / beyond authority (Detournement de Pouvoir) with traits beyond the tenure or deadline for authorization, beyond the territorial limits of authority; and / or contrary to the provisions of the legislation. The act of Herman Adi AW as a Budget User is an act that is contrary to the provisions of the laws and regulations that are specifically regulated in Article 5 of Presidential Regulation Number 54 of 2010 along with its amendments, especially the principles of transparency, competition and accountability.The Budget User's legal responsibility for abuse of authority in the procurement of goods in Brebes Regency can be subject to criminal sanctions, namely that criminal responsibility for abuse of authority is regulated in Article 3 of the Corruption Act. Herman Adi Aw as a budget user who is proven to be corrupt with a prison sentence of 1 (one) year and 6 (six) months, as well as a fine of Rp. 50,000,000.00 (fifty million rupiah). Based on civil liability Herman Adi Aw as the Budget User is obliged to return compensation. Based on the administrative aspect, the Brebes Regency Government issued the Brebes Regent Decree No. 887/080 of 2014 as of January 24, 2014 temporarily suspending the position of Herman Adi AW in his position as the Head of the Industry Office.